Method for modifying surface of PEEK (Polyether Ether Ketone) substrate and improving binding force of PEEK substrate and conductive metal layer
The modified PEEK substrate surface is treated with laser and concentrated sulfuric acid and printed conductive nanosilver layer on it, which solves the problem of poor bonding performance between PEEK substrate and conductive ink, and improves the conductivity and stability of electronic components.
Patent Information
- Application Number
- CN202411239119.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-27
AI Technical Summary
In the field of electronic additive manufacturing, the poor bonding performance of PEEK substrates and conductive inks leads to poor ink adhesion performance, affecting the signal transmission and loss performance of electronic components.
The surface of PEEK substrate was modified by laser treatment and concentrated sulfuric acid vulcanization reaction to improve the surface roughness and chemical reactivity, and a conductive nanosilver layer was printed on the modified surface, and the binding force was enhanced by sintering and curing.
The bonding force between the PEEK substrate and the conductive metal layer is significantly improved, the physical adsorption and chemical combination of the material is enhanced, the conductive and overall performance is improved, and the problem of poor ink adhesion performance is solved.
Smart Images

Figure CN119187592A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic additive manufacturing, and in particular to a method for surface modification of a PEEK substrate and improving the bonding strength thereof with a conductive metal layer. Background Art
[0002] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.
[0003] Currently, many types of substrates have been used for 3D printing electronic devices, such as polyethylene terephthalate (PET), polyimide (PI), epoxy resin (EP), polyetheretherketone (PEEK), etc. As electronic components develop towards high integration and miniaturization, especially in the aerospace field, more stringent requirements are placed on the mechanical strength, stiffness and weight of electrical structural parts. PEEK has been widely used in medical implants and bioengineering due to its excellent fatigue resistance, heat resistance, chemical resistance, and extremely light weight, but there are few studies on the application of PEEK in the field of electronic additive manufacturing, especially in 3D printing of electronic devices.
[0004] In industrial manufacturing, the conductive circuits of electronic devices are usually produced by screen printing, gravure printing and offset lithography. For example, the edges of the circuits produced by screen printing are uneven, the precision is poor, and the cost is high; gravure printing and offset lithography can only be printed on a flat surface and cannot produce conformal electronic structures. Inkjet printing (IJP) technology in 3D printing can effectively improve this problem. It has almost no restrictions on the shape of the printed substrate and is a widely used technology for making conductive layers. For electronic devices, whether the conductive circuit and the substrate material are firmly bonded has a great impact on signal transmission and loss performance. Strong bonding can reduce contact resistance and improve the stability and life of electronic components. When IJP and PEEK substrates are combined to manufacture electronic components, the low surface free energy and inherent hydrophobic properties of PEEK hinder its ability to form a strong bond with materials such as conductive inks, resulting in poor ink adhesion. Therefore, the modification of the surface of the PEEK substrate becomes a key factor in improving the bonding performance between the interface and the conductive ink.
[0005] In order to improve the bonding force between the PEEK substrate and its surface metal layer, the technologies for PEEK surface treatment include plasma treatment, chemical treatment, mechanical grinding and laser treatment. These methods aim to change the surface chemistry or surface morphology of PEEK to improve adhesion with the coating. Among them, concentrated sulfuric acid has been recognized as an effective treatment method that can improve the surface properties of various materials and improve their wettability, bonding and overall performance. The sulfonation reaction will cause changes in the microstructure of the polyetheretherketone material, especially the formation of a porous network. The longer the sulfonation time, the more obvious the porous structure, which is more conducive to the adhesion of ink droplets. In addition, the laser has the advantages of high precision, high efficiency, no pollution and good coherence. In particular, it can guide the modification of the specified surface area to change the physical and chemical properties of the substrate, thus having unique process technology advantages. A large number of studies have shown that the use of laser modification technology can improve the interfacial bonding properties of PEEK substrates.
[0006] Therefore, the bonding performance between modified PEEK substrate and heterogeneous materials in the field of electronic additive manufacturing needs to be studied urgently. Summary of the invention
[0007] The purpose of the present invention is to provide a method for surface modification of a PEEK substrate and improving the bonding strength with a conductive metal layer in order to solve the problem of poor ink adhesion when combining piezoelectric inkjet technology (IJP) and a PEEK substrate in the current electronic additive manufacturing field to manufacture electronic components. The method can effectively improve the chemical inertness of the PEEK substrate, which has a large contact angle and low surface free energy, and has a significant effect on improving the bonding performance between the PEEK substrate and heterogeneous materials.
[0008] The technical solution of the present invention is as follows:
[0009] A method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer, comprising:
[0010] Step S1: preparing a PEEK substrate sample;
[0011] Step S2: performing a basic polishing process on the PEEK substrate sample;
[0012] Step S3: cleaning and drying the PEEK substrate sample after the polishing process;
[0013] Step S4: placing the dried PEEK substrate sample under a laser for laser treatment to produce a microstructure with a microstructure;
[0014] Step S5: placing the laser-treated PEEK substrate sample in concentrated sulfuric acid to perform a vulcanization reaction to modify the surface of the PEEK substrate sample;
[0015] Step S6: cleaning the surface-modified PEEK substrate sample and drying it;
[0016] Step S7: printing a conductive metal layer on the surface of the PEEK substrate sample after drying;
[0017] Step S8: performing sintering and curing treatment on the conductive metal layer.
[0018] Furthermore, the step S1 comprises:
[0019] Several sets of PEEK substrate samples were printed using an FDM printer.
[0020] Furthermore, the step S2 comprises:
[0021] The PEEK substrate samples were sanded using silicon carbide sandpaper.
[0022] Furthermore, the step S3 comprises:
[0023] Ultrasonic cleaning was performed using anhydrous ethanol, acetone solution and deionized water respectively. After cleaning, the mixture was dried in a vacuum and hermetically sealed.
[0024] Furthermore, the step S4 comprises:
[0025] The PEEK substrate sample was placed under UV laser process, and the scanning parameters were set to process a micro-morphology with a microstructure. The treated PEEK substrate sample was ultrasonically cleaned in anhydrous ethanol solution, acetone solution, and deionized water respectively. After cleaning, it was placed in a vacuum to dry and hermetically seal.
[0026] Furthermore, the step S5 comprises:
[0027] The PEEK substrate samples were immersed in concentrated sulfuric acid at ambient temperature. After the preset reaction time, the samples were immediately transferred to deionized water to terminate the reaction.
[0028] Furthermore, the step S6 comprises:
[0029] The PEEK substrate samples were ultrasonically cleaned in anhydrous ethanol solution, acetone solution, and deionized water, respectively. After cleaning, they were dried in a vacuum and hermetically sealed.
[0030] Furthermore, the conductive metal layer is a conductive nanosilver layer.
[0031] Furthermore, the step S7 comprises:
[0032] A conductive nanosilver layer was printed on the PEEK substrate sample using a piezoelectric inkjet 3D printing device.
[0033] Furthermore, the step S8 comprises:
[0034] The PEEK substrate sample with the conductive nanosilver layer was placed under an infrared light radiation source and subjected to rapid sintering exposure, and the process was repeated multiple times to ensure thorough sintering.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The surface modification treatment of the PEEK sample adopted in the present invention, i.e., first using laser and then using concentrated sulfuric acid to modify the surface of PEEK, can effectively improve the roughness of the PEEK surface, reduce the water contact angle of the surface, thereby increasing its surface area, and help to enhance the physical adsorption and chemical bonding of the material with other materials, thereby improving the coating, bonding or coating effect;
[0037] 2. The treated PEEK surface of the present invention exposes more active functional groups, increasing the chemical reactivity of the surface. This helps to achieve stronger chemical bonding, thereby improving the performance and stability of the material;
[0038] 3. The treated PEEK surface of the present invention increases the bonding force with the nanosilver conductive layer on its surface, making it more firmly bonded. This enhanced bonding force helps to ensure good contact between the conductive layer and the substrate, thereby improving the conductive performance and overall performance;
[0039] 4. Through surface modification, the PEEK substrate not only retains its original excellent properties, such as high temperature stability, chemical stability and mechanical properties, but also increases its compatibility and bonding with other materials, making it have a wider range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a flow chart of a method for surface modification of a PEEK substrate and improving the bonding strength between the substrate and a conductive metal layer according to the present invention;
[0041] Figure 2 It is a relationship diagram between the concentrated sulfuric acid treatment time of a PEEK substrate surface modification method and a method for improving the bonding strength with a conductive metal layer of the present invention and the bonding strength and roughness of the PEEK substrate sample surface;
[0042] Figure 3 The diagram is a relationship diagram between the UV laser speed and the surface bonding force and roughness of the PEEK substrate sample in a method for surface modification of a PEEK substrate and improving the bonding force with a conductive metal layer of the present invention. DETAILED DESCRIPTION
[0043] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0044] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0045] Embodiment 1
[0046] The process of the present invention is as follows Figure 1 As shown, the method includes five steps: using FDM technology to print out a PEEK substrate sample, polishing the surface of the PEEK substrate sample, laser treating the PEEK substrate sample and treating it with concentrated sulfuric acid, printing a nanosilver conductive layer on the surface of the surface-modified PEEK substrate sample, and sintering and curing the nanosilver conductive layer. The surface modification of the PEEK substrate sample is achieved, the surface roughness is increased, the surface contact angle is reduced, and the active functional groups are increased. Therefore, the bonding force between the surface of the PEEK substrate sample and the nanosilver layer is effectively improved, providing a practical method for the field of electronic additive manufacturing.
[0047] For details, please participate Figure 1-Figure 3 A method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer comprises the following detailed steps:
[0048] Step S1: preparing a PEEK substrate sample;
[0049] Step S2: performing a basic polishing process on the PEEK substrate sample;
[0050] Step S3: cleaning and drying the PEEK substrate sample after the polishing process;
[0051] Step S4: placing the dried PEEK substrate sample under a laser for laser treatment to produce a microstructure with a microstructure;
[0052] Step S5: placing the laser-treated PEEK substrate sample in concentrated sulfuric acid to perform a vulcanization reaction to modify the surface of the PEEK substrate sample;
[0053] Step S6: cleaning the surface-modified PEEK substrate sample and drying it;
[0054] Step S7: printing a conductive metal layer on the surface of the PEEK substrate sample after drying;
[0055] Step S8: performing sintering and curing treatment on the conductive metal layer.
[0056] In this embodiment, specifically, step S1 includes:
[0057] Multiple sets of PEEK substrate samples were printed using an FDM printer; in this embodiment, specifically, the FDM was used to make the PEEK substrate samples with the following settings: a printing temperature of 440°C, a hot bed substrate temperature of 130°C, and a chamber temperature of 90°C. The layer height was set to 0.15 mm, and the samples were printed at a printing speed of 60 mm / s using a 100% filling density.
[0058] In this embodiment, specifically, step S2 includes:
[0059] The PEEK substrate sample was sanded using silicon carbide (SiC) sandpaper to ensure consistent surface roughness of the entire sample; that is, in order to reduce the inherent surface roughness imparted by 3D printing, the printed PEEK substrate sample was subjected to a basic polishing process; in this embodiment, specifically, the PEEK substrate sample was sanded using silicon carbide (SiC) sandpaper in sequence, starting from 240 mesh to 3000 mesh, to ensure consistent surface roughness of the entire sample; the polished sample clearly showed hydrophobicity, and the contact angle value measured by a contact angle meter was 105.78°.
[0060] In this embodiment, specifically, step S3 includes:
[0061] Ultrasonic cleaning was performed for 10 min using anhydrous ethanol, acetone solution and deionized water respectively. After cleaning, the mixture was dried at 70°C in a vacuum and hermetically sealed.
[0062] In this embodiment, specifically, step S4 includes:
[0063] The PEEK substrate sample is placed under a UV laser process, and the scanning parameters are set to process a micro-morphology with a microstructure, and the treated PEEK substrate sample is placed in anhydrous ethanol solution, acetone solution, and deionized water for ultrasonic cleaning for 10 minutes. After cleaning, it is placed in a vacuum at 70°C to dry and hermetically seal; that is, the laser marking machine equipped with a 355nm ultraviolet pulse laser system in this embodiment scans the PEEK substrate sample, and while adjusting the scanning speed, other processing parameters remain consistent: the scan is performed once, the line spacing is 0.05mm, the current is 1 ampere, and the frequency is set to 30kHz; the operating distance of the laser is maintained at 14cm; in this embodiment, specifically, the UV laser is a laser with a wavelength band of 150-600nm, and the laser scanning speed range is 600-3000mm / s, among which a scanning speed of 1500mm / s has a better effect.
[0064] In this embodiment, specifically, step S5 includes:
[0065] The PEEK substrate sample is immersed in concentrated sulfuric acid at ambient temperature. After reaching the preset reaction time, the sample is immediately transferred to deionized water to terminate the reaction; in this embodiment, specifically, the concentrated sulfuric acid has a concentration of 95%-98%, and the concentrated sulfuric acid treatment time ranges from 30 to 300 seconds, wherein a treatment time of 120 seconds has a better effect;
[0066] It should be noted that the surface roughness of the PEEK substrate sample treated with laser and concentrated sulfuric acid increased significantly from 0.20μm after polishing to 3.25μm. Laser treatment will cause ordered laser pits to appear on the surface of the PEEK substrate sample. After concentrated sulfuric acid treatment, the ordered laser pits will be transformed into a complex morphology of random pits, pores, and grooves. In the surface chemical composition, the O / C ratio is 26.05%, the CO bond increases significantly to 50.58%, and the CC bond decreases to 46.53%, indicating that oxidation is enhanced and hydrophilicity may increase. The water contact angle increases to 85.64°, showing a moderate increase in hydrophilicity.
[0067] In this embodiment, specifically, step S6 includes:
[0068] The PEEK substrate samples were ultrasonically cleaned in anhydrous ethanol solution, acetone solution, and deionized water for 10 min, respectively. After cleaning, they were dried at 70°C in a vacuum and hermetically sealed to ensure that the PEEK samples were free of excess impurities.
[0069] In this embodiment, specifically, the conductive metal layer is a conductive nanosilver layer.
[0070] In this embodiment, specifically, step S7 includes:
[0071] A 30×30 mm, 2 μm thick conductive nanosilver layer was printed on a PEEK substrate sample using a piezoelectric inkjet 3D printing device; in this embodiment, specifically, the experimental parameters for printing the conductive nanosilver layer were: a nozzle aperture of 60 μm and a working pressure of 0.4 MPa. During printing, the device maintained a steady speed of 10 mm / s, rhythmically sprayed droplets at a frequency of 150 Hz, and the temperature of the hot bed substrate was 100°C during the entire printing process.
[0072] In this embodiment, specifically, step S8 includes:
[0073] The PEEK substrate sample with the conductive nanosilver layer was placed 4 cm away from the radiation source and subjected to a rapid 3-second sintering exposure, and the process was repeated 5 times to ensure thorough sintering to effectively improve its mechanical strength and conductive properties.
[0074] It should also be noted that the bonding strength between the PEEK substrate sample and the conductive nano-silver layer was measured using a digital pull-off adhesion tester. It was found that the bonding strength between the polished PEEK substrate sample and the nano-silver layer on its surface was only 0.37 MPa, and the bonding strength between the PEEK substrate sample that was first treated with laser and then with concentrated sulfuric acid and the nano-silver layer on its surface was 2.77 MPa, which was increased by about 7.5 times.
[0075] Embodiment 2
[0076] Example 2 According to the process in Example 1, the following specific example was carried out using piezoelectric inkjet 3D printing technology according to the following steps:
[0077] 1. Use FDM printer to print out multiple sets of PEEK samples with sample size of 50mm×50mm×4mm;
[0078] 2. Use silicon carbide (SiC) sandpaper to perform basic polishing process on the printed PEEK substrate;
[0079] 3. The polished PEEK samples were subjected to ultrasonic baths in acetone, ethanol, and deionized water for 10 min each, and then the samples were dried under vacuum at 70 °C and hermetically sealed;
[0080] 4. Use a laser marking machine equipped with a 355nm ultraviolet pulse laser system to perform surface laser treatment on the polished PEEK sample. Set the UV laser scanning speed to 1500mm / s. After scanning, place the laser-treated PEEK sample in an ultrasonic bath in acetone, ethanol, and deionized water for 10 minutes each. Then, dry the sample under vacuum at 70°C and seal it airtightly.
[0081] 5. Treat the laser-treated PEEK substrate with concentrated sulfuric acid, immerse it in concentrated sulfuric acid at ambient temperature, set the reaction time to 30s, and immediately transfer the sample to deionized water to terminate the reaction after the reaction time is reached. The PEEK sample treated with concentrated sulfuric acid was subjected to an ultrasonic bath in acetone, ethanol, and deionized water for 10 minutes each, and then the sample was dried under vacuum at 70°C and sealed airtight;
[0082] 6. Use a piezoelectric inkjet 3D printing device to print a 30×30 mm, 2 μm thick nanosilver layer on the surface of three PEEK samples;
[0083] 7. Sintering and curing the nano silver layer.
[0084] The surface modification method of the PEEK sample provided by the method of the present invention has been experimentally verified to be a surface modification method of laser treatment followed by concentrated sulfuric acid treatment to improve the surface roughness of PEEK, and effectively increase the bonding area between the printed ink droplets and the PEEK surface. At the same time, the reaction generates more active functional groups, increases the chemical reaction activity of the surface, improves the bonding force between the PEEK substrate and the conductive metal layer, and effectively solves the problem of poor adhesion of nanosilver ink on the PEEK surface. The above-described embodiments only express the specific implementation methods of the present application, and the description is relatively specific and detailed, but it cannot be understood as a limitation on the scope of protection of the present application. It should be pointed out that for those of ordinary skill in the art, without departing from the concept of the technical solution of the present application, several deformations and improvements can also be made, which all belong to the scope of protection of the present application.
[0085] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.
Claims
1. A method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer, characterized in that: include: Step S1: preparing a PEEK substrate sample; Step S2: performing a basic polishing process on the PEEK substrate sample; Step S3: cleaning and drying the PEEK substrate sample after the polishing process; Step S4: placing the dried PEEK substrate sample under a laser for laser treatment to produce a microstructure with a microstructure; Step S5: placing the laser-treated PEEK substrate sample in concentrated sulfuric acid to perform a vulcanization reaction to modify the surface of the PEEK substrate sample; Step S6: cleaning the surface-modified PEEK substrate sample and drying it; Step S7: printing a conductive metal layer on the surface of the dried PEEK substrate sample; Step S8: performing sintering and curing treatment on the conductive metal layer.
2. The method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer according to claim 1, characterized in that: The step S1 comprises: Several sets of PEEK substrate samples were printed using an FDM printer.
3. The method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer according to claim 1, characterized in that: The step S2 comprises: The PEEK substrate samples were sanded using silicon carbide sandpaper.
4. The method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer according to claim 1, characterized in that: The step S3 comprises: Ultrasonic cleaning was performed using anhydrous ethanol, acetone solution and deionized water respectively. After cleaning, the mixture was dried in a vacuum and hermetically sealed.
5. The method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer according to claim 1, characterized in that: The step S4 comprises: The PEEK substrate sample was placed under UV laser process, and the scanning parameters were set to process a micro-morphology with a microstructure. The treated PEEK substrate sample was ultrasonically cleaned in anhydrous ethanol solution, acetone solution, and deionized water respectively. After cleaning, it was placed in a vacuum to dry and hermetically sealed.
6. The method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer according to claim 1, characterized in that: The step S5 comprises: The PEEK substrate samples were immersed in concentrated sulfuric acid at ambient temperature. After the preset reaction time, the samples were immediately transferred to deionized water to terminate the reaction.
7. The method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer according to claim 1, characterized in that: The step S6 comprises: The PEEK substrate samples were ultrasonically cleaned in anhydrous ethanol solution, acetone solution, and deionized water, respectively. After cleaning, they were dried in a vacuum and hermetically sealed.
8. The method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer according to claim 1, characterized in that: The conductive metal layer is a conductive nano-silver layer.
9. The method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer according to claim 8, characterized in that: The step S7 comprises: A conductive nanosilver layer was printed on the PEEK substrate sample using a piezoelectric inkjet 3D printing device.
10. The method for surface modification of a PEEK substrate and improving the bonding strength between the PEEK substrate and a conductive metal layer according to claim 9, characterized in that: The step S8 comprises: The PEEK substrate sample with the conductive nanosilver layer was placed under an infrared light radiation source and subjected to rapid sintering exposure, and the process was repeated multiple times to ensure thorough sintering.
